Composite carbon layer coated graphite matched silicon carbon material and preparation method thereof
Through the preparation method of composite carbon layer coated with graphite to match silicon carbon materials, the problem of low energy density of graphite negative electrodes and unstable electrode structure in lithium-ion batteries in lithium-ion batteries is solved, and the effect of improving battery charge and discharge efficiency and extending battery life is achieved.
Patent Information
- Application Number
- CN202510346251.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-24
AI Technical Summary
The energy density of graphite negative electrodes in lithium-ion batteries is low, and when mixed with graphite, the silicon-based negative electrodes will lead to problems such as unstable electrode structure, lithium-ion crosstalk and shortened battery life.
The preparation method of composite carbon layer coated with graphite matched silicon carbon materials is adopted to form graphite nanobridged structures by asphalt coated graphite substrate and chemical vapor deposition, and mixed with the silicon carbon substrate to form a composite material with a porous structure.
It improves the charging and discharging efficiency and battery life of the battery, enhances the overall conductive performance and mechanical stability of the material, and alleviates the volume expansion effect of silicon during the charging and discharging process.
Smart Images

Figure CN119858914A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite carbon layer-coated graphite-matched silicon-carbon material and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, lithium-ion batteries, as an efficient and portable energy storage device, have extensive and critical applications in many fields such as electric vehicles and portable electronic devices. At present, graphite is one of the most commonly used negative electrode materials for lithium-ion batteries. It has many advantages, such as good conductivity, stable chemical properties and relatively mature preparation technology, which makes it occupy an important position in the commercialization process of lithium-ion batteries. However, the graphite negative electrode also has a significant shortcoming, that is, its energy density is relatively low. In the pursuit of higher energy density to meet the needs of fields such as long-range electric vehicles, this limitation is becoming more and more prominent. It is difficult to achieve a breakthrough improvement in the performance of lithium-ion batteries by relying solely on graphite as a negative electrode material.
[0003] In order to overcome the problem of low energy density of graphite negative electrode, the introduction of silicon-based negative electrode has become a research hotspot. From a theoretical perspective, silicon-based materials have extremely high specific capacity and have the potential to significantly increase battery energy density compared to graphite. In view of the problem of insufficient energy density of graphite negative electrode, the introduction of silicon-based negative electrode materials has become the focus of current research. Silicon-based negative electrode has extremely high specific capacity and has the potential to significantly increase battery energy density compared to graphite.
[0004] However, if the silicon-based negative electrode is simply mixed with graphite, a series of thorny problems will arise: (1) From the perspective of the material's own characteristics, the volume expansion of silicon during the charge and discharge process is extremely significant. Compared with graphite, the radius of silicon atoms is relatively large. When lithium ions are embedded and extracted, the silicon lattice will undergo drastic deformation, and its volume expansion rate can be as high as 300%~400%. When mixed directly with graphite, this large volume change will cause serious damage to the overall structure of the electrode. On the one hand, it will cause cracks and pores inside the electrode material, making the contact between the active material and the current collector worse, obstructing the electron conduction path, and increasing the internal resistance of the battery; on the other hand, the instability of the electrode structure will also cause the active material to fall off, reducing the charge and discharge capacity of the battery.
[0005] (2) There are also essential differences between graphite and silicon in terms of electrochemical performance. Graphite has a relatively stable charge and discharge potential platform, and the process of lithium ion embedding and extraction between graphite layers is relatively gentle, following a relatively stable diffusion mechanism. However, the charge and discharge potential range of silicon is different from that of graphite, and its electrochemical reaction kinetics is more complicated, and the rate of lithium ion embedding and extraction is inconsistent with that of graphite. After a simple mixture of the two, the potential distribution in different areas of the electrode is uneven during the charge and discharge cycle, resulting in an increase in polarization. The generation of polarization requires a higher voltage when charging the battery and a lower voltage when discharging, resulting in ineffective energy loss and directly reducing the battery's charge and discharge efficiency.
[0006] (3) From the perspective of lithium ion transmission, due to the different microstructures of graphite and silicon, the diffusion coefficients of lithium ions in the two are quite different. Graphite has a regular layered structure, which is conducive to the rapid diffusion of lithium ions between layers; the crystal structure of silicon is relatively complex, and the diffusion resistance of lithium ions in it is relatively large. After mixing, during charging and discharging, lithium ions will preferentially choose graphite areas with low diffusion resistance to embed and detach, resulting in excessive local lithium ion concentration, forming a concentration gradient, and inducing lithium ion crosstalk. Lithium ion crosstalk not only disrupts the normal charging and discharging sequence, deforming the battery's charging and discharging curve, but also accelerates the attenuation of battery capacity. Because lithium ions gather in unexpected areas, they may react with the electrolyte to generate some lithium salt deposits that are difficult to decompose. These deposits adhere to the electrode surface, further hindering lithium ion transmission, forming a vicious cycle, and ultimately leading to a significant shortening of battery life. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a composite carbon layer coated graphite matching silicon-carbon material and a preparation method thereof, aiming to solve the problem of reduced battery charge and discharge capacity and charge and discharge efficiency and shortened battery life.
[0008] To solve the above technical problems, the present invention is implemented as follows: the present invention provides a method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material, the steps comprising: S1, coating asphalt on a graphite substrate to obtain coated graphite; S2, introducing a carbon source gas to perform chemical vapor deposition on the coated graphite, generating a graphite nano-bridge structure with a specific orientation on the surface of the coated graphite, and obtaining modified graphite; S3, preparing a silicon-carbon substrate and mixing it with the modified graphite to obtain a composite carbon layer-coated graphite-matched silicon-carbon material.
[0009] In some embodiments of the present invention, in step S1, the graphite substrate includes at least one of natural graphite, primary graphite particles, secondary graphite particles, needle coke graphite, petroleum coke graphite, raw coke graphite, and cooked coke graphite, and the asphalt includes β resin, and the content of the β resin in the asphalt is 10-80%.
[0010] In some embodiments of the present invention, step S1 comprises: S1.1. Ultrasonic dispersion of asphalt in anhydrous ethanol for 15 to 60 minutes to form an asphalt emulsion; S1.2, transfer the asphalt emulsion to a constant temperature water bath, add the graphite substrate to the asphalt emulsion under the condition of controlling the temperature at 40-90°C, control the stirring speed at 300-500 rpm, and continue stirring for 1-3 hours until the anhydrous ethanol is completely evaporated; S1.3. After stirring, transfer to a vacuum oven and continue vacuum drying at 60-80°C for 12-24 hours to obtain coated graphite.
[0011] In some embodiments of the present invention, step S1 comprises: S1.1, preheating the asphalt to 80-120°C and stirring for 30-90 minutes, while adding graphene or carbon nanotubes to obtain rheological asphalt; S1.2. The rheological asphalt and the graphite substrate are mixed in the solid phase in a VC mixer. The revolution speed of the VC mixer is set to 30-150 r / min, the rotation speed is set to 50-200 r / min, and the mixing time is set to 0.5-5 hours. During the mixing process, ultrasonic assisted dispersion with a frequency of 20-40 kHz is intermittently used. The ultrasonic treatment time for each time is 10-20 minutes. After the mixing is completed, the coated graphite is obtained.
[0012] In some embodiments of the present invention, calculated by weight percentage, in the coated graphite, the asphalt accounts for 10-40wt%, and the graphite substrate accounts for 60-90%.
[0013] In some embodiments of the present invention, step S2 comprises: S2.1, the coated graphite is evenly laid in a quartz boat, and then the quartz boat is placed in a constant temperature zone of a tube furnace, the tube furnace is evacuated, and an inert gas is introduced; S2.2, raising the temperature to 500-1400°C at a heating rate of 0.5-5°C / min, maintaining the temperature and continuously introducing carbon source gas for chemical vapor deposition, adjusting the ambient pressure to 10-50 Pa, and controlling the deposition time to 30-120 minutes, to generate a graphite nano-bridge structure oriented in the same direction as the gas flow; S2.3. After the deposition is completed, stop introducing the carbon source gas and introduce only the inert gas. Keep the temperature for 1 to 20 hours, then slowly cool the temperature to 100 to 800°C at a cooling rate of 0.5 to 5°C / min, and then naturally cool the temperature to room temperature to obtain modified graphite.
[0014] In some embodiments of the present invention, in step S2, the inert gas includes at least one of nitrogen, argon, and hydrogen, the flow rate of the inert gas is 1~20L / min, and the carbon source gas includes at least one of ethylene and hydrogen in a volume ratio of 2:1, methane and hydrogen in a volume ratio of 4:1, and acetylene and hydrogen in a volume ratio of 1:1.
[0015] In some embodiments of the present invention, step S3 includes: S3.1, mixing the porous carbon precursor with the silicon source material, raising the temperature to 400-700°C at 2-5°C / min under the protection of an inert gas, and keeping the temperature for 2-4 hours to obtain a silicon-carbon substrate; S3.2. Mix the silicon-carbon substrate and the modified graphite in a VC mixer at a specific mass ratio, set the VC mixer revolution speed to 20-120 r / min, rotation speed to 40-180 r / min, mix for 0.5-~4 hours, and obtain a composite carbon layer-coated graphite matching silicon-carbon material.
[0016] In some embodiments of the present invention, in step S3, the porous carbon precursor includes at least one of biomass carbon, asphalt carbon, and resin carbon, and the silicon source material includes at least one of sodium silicate, tetraethoxysilane, and nano-silicon powder. Calculated by mass ratio, the porous carbon precursor: the silicon source = (2~5): 1, and the silicon-carbon substrate includes internal pores and nano-silicon particles located in the internal pores, the size of the nano-silicon particles is 0.1~50nm, and the size of the internal pores is 0.1~100nm.
[0017] The present invention provides a composite carbon layer-coated graphite-matched silicon-carbon material, which is prepared by the preparation method of the composite carbon layer-coated graphite-matched silicon-carbon material as described above, wherein the composite carbon layer-coated graphite-matched silicon-carbon material comprises asphalt, a graphite substrate, a graphite nano-bridging structure, and a silicon-carbon substrate; wherein, The pitch is used to form a coated carbon layer and optimize the interface bonding between the coated carbon layer and the graphite substrate; The graphite substrate is used to provide a stable conductive skeleton and structural support; The graphite nano-bridge structure is used to strengthen the conductive network, enhance the overall structural stability and conductive properties of the material, and effectively buffer the stress of lithium ions during the charging and discharging process; The silicon-carbon substrate is used to increase the theoretical specific capacity of the entire material and buffer the volume expansion of silicon during the charge and discharge process.
[0018] Compared with the prior art, the composite carbon layer-coated graphite-matched silicon-carbon material and the preparation method thereof in the present invention have the following beneficial effects: In step S1, asphalt is coated on the surface of the graphite substrate, and the asphalt is carbonized under high temperature conditions to generate a carbon layer with good conductivity. The carbon layer can enhance the electrical contact between the graphite substrates, improve the overall electron migration rate, and effectively optimize the interface between graphite and the electrolyte, and improve the integrity of the conductive network, thereby improving the charge and discharge efficiency and battery life. The carbon layer can prevent the electrolyte from directly reacting with the graphite, reduce side reactions, and the stable interface reduces irreversible lithium loss and maintains the effective utilization of active lithium ions. In step S2, the graphite nano-bridge structure generated by chemical vapor deposition can optimize the electronic and ion transmission paths of the material at the microscopic level, while alleviating the volume expansion effect of the battery: the graphite nano-bridge structure builds a three-dimensional electron migration path at the microscopic scale and shortens the electron diffusion distance. Even under high-rate charge and discharge conditions, it can maintain a low resistance and ensure rapid electron transport. The graphite nano-bridge structure provides mechanical support for the silicon-carbon substrate to prevent silicon from pulverizing due to volume expansion during the charge and discharge process. The structural integrity maintains the conductive path of the electrode and extends the cycle life. The ordered orientation of the graphite nano-bridging structure can optimize the insertion and extraction paths of lithium ions. It reduces the risk of lithium dendrite formation, prevents short circuits and capacity attenuation, and improves charge and discharge capacity and stability. In step S3, the silicon-carbon substrate is mixed with modified graphite to form a composite material with a porous structure, which takes into account both high capacity and structural stability. Through the compounding of silicon with graphite, the high capacity characteristics of silicon can be fully released. The carbon layer and the graphite nano-bridging structure work together to absorb the stress generated by volume expansion. The graphite nano-bridging structure provides an electron transmission path, and the pores of the silicon-carbon substrate provide a diffusion path for lithium ions. The synchronization of electron and ion transmission improves the overall charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a TEM image of a composite carbon layer coated with graphite matching silicon-carbon material in one embodiment of the present invention; Figure 2 1 is an XRD diagram of an embodiment and a comparative example of a composite carbon layer coated with graphite matching silicon-carbon material in one embodiment of the present invention; Figure 3 It is a Raman spectrum diagram of an embodiment and a comparative example of a composite carbon layer coated with graphite matching silicon-carbon material in one embodiment of the present invention. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] The present invention provides a method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material, the steps comprising: S1. Coating asphalt on a graphite substrate to obtain coated graphite. The graphite substrate includes at least one of natural graphite, primary graphite particles, secondary graphite particles, needle coke graphite, petroleum coke graphite, raw coke graphite, and cooked coke graphite. The asphalt includes β resin, and the content of β resin in the asphalt is 10-80%. Calculated by weight percentage, in the coated graphite, the asphalt accounts for 10-40wt%, and the graphite substrate accounts for 60-90%.
[0022] In one embodiment, step S1 includes: S1.1. Ultrasonic disperse the asphalt in anhydrous ethanol for 15 to 60 minutes to form an asphalt emulsion.
[0023] By ultrasonically dispersing asphalt in anhydrous ethanol, the aggregation state of asphalt can be effectively destroyed to form a uniform and fine emulsion. This helps to improve the contact uniformity and interface bonding strength between asphalt and graphite substrate in subsequent steps, thus laying the foundation for the formation of a continuous coating layer.
[0024] S1.2. Transfer the asphalt emulsion to a constant temperature water bath. When the temperature is controlled at 40-90°C, add the graphite substrate into the asphalt emulsion. Control the stirring speed at 300-500 rpm and continue stirring for 1-3 hours until the anhydrous ethanol is completely evaporated.
[0025] In a constant temperature water bath, adding the graphite substrate to the asphalt emulsion and mixing at a moderate stirring speed is conducive to the asphalt coating the graphite surface evenly. Temperature control and stirring uniformity ensure the full volatilization of ethanol, so that the asphalt is deposited on the graphite surface to form a stable initial coating layer, improving the stability of subsequent carbonization and the overall structure of the material.
[0026] S1.3. After stirring, transfer to a vacuum oven and continue vacuum drying at 60-80°C for 12-24 hours to obtain coated graphite. Drying the mixed material in a vacuum oven can completely remove the residual solvent and avoid thermal degradation and oxidation of asphalt in a low-temperature vacuum environment. The final coated graphite has a uniform and firm asphalt coating layer, which provides a high-quality precursor for subsequent heat treatment and carbonization processes, and enhances the overall conductivity and mechanical stability of the material.
[0027] β-resin is a resin component with excellent film-forming properties, adhesion and thermal stability, and exists as an active component in asphalt. Its molecular structure is stable, and it can maintain its shape and transform into a carbon structure at high temperatures, thereby forming a dense carbon layer during the subsequent heat treatment process.
[0028] The advantages of coating the graphite substrate by the liquid phase method are that the ultrasonic dispersion makes the β resin in the asphalt emulsion evenly dispersed, ensuring the formation of a continuous and uniform coating layer on the graphite surface. The temperature-controlled water bath method is conducive to the precise control of the asphalt deposition and ethanol volatilization process, avoiding local overheating or uneven deposition caused by high temperature. Uniform coating can improve the adhesion between the asphalt and the graphite substrate, forming a strong interface and providing a stable precursor for subsequent carbonization. After vacuum drying, the formed coating layer is more conducive to the formation of a dense and highly conductive carbon layer during the carbonization process, thereby optimizing the mechanical and electrochemical properties of the final composite material.
[0029] In one embodiment, step S1 includes: S1.1. Preheat the asphalt to 80-120°C and keep stirring for 30-90 minutes, and add graphene or carbon nanotubes to obtain rheological asphalt.
[0030] Preheating to 80-120°C changes the asphalt from a high-viscosity solid state to a rheological state, reduces flow resistance, and creates conditions for uniform dispersion. Graphene or carbon nanotubes are added during the stirring process. These nanomaterials with high conductivity and enhanced mechanical properties are easy to disperse evenly at high temperatures, thereby forming a modified asphalt matrix and improving the conductivity and mechanical strength of the subsequent coating layer. Preheating and sufficient stirring can promote the interaction between the β-resin component and the nanomaterial in the asphalt, forming a mixture with better rheological properties and bonding ability, providing a better quality precursor for subsequent solid phase coating.
[0031] S1.2. The rheological asphalt and the graphite substrate are mixed in the solid phase in a VC mixer. The revolution speed of the VC mixer is set to 30-150 r / min, the rotation speed is set to 50-200 r / min, and the mixing time is set to 0.5-5 hours. During the mixing process, ultrasonic assisted dispersion with a frequency of 20-40 kHz is intermittently used. The ultrasonic treatment time for each time is 10-20 minutes. After the mixing is completed, the coated graphite is obtained.
[0032] By using solid phase mixing in the VC mixer, the modified asphalt and the graphite substrate are fully contacted and evenly dispersed by setting reasonable revolution and rotation speeds (30150r / min and 50200r / min) and a mixing time of 0.5~5 hours. Intermittent ultrasonic treatment at 2040kHz, 1020 minutes each time, effectively breaks up the tiny agglomerates that may be formed on the surface of the asphalt and graphite, improves the mixing uniformity, and enhances the interfacial adhesion. After solid phase mixing, the modified asphalt can be evenly coated on the surface of the graphite substrate to form a continuous and dense coating layer, which is conducive to the formation of a stable and highly conductive carbon layer during the subsequent heat treatment process.
[0033] Advantages of solid phase coating: The combination of VC mixer and ultrasonic assisted dispersion effectively overcomes the problem of local unevenness, making the interface contact between asphalt and graphite closer. Uniform coating can form a continuous precursor layer, which is converted into a dense carbon layer during the subsequent heat treatment process, thereby improving the overall mechanical strength, conductivity and cycle stability of the composite material.
[0034] S2. A carbon source gas is introduced to perform chemical vapor deposition on the coated graphite to generate a graphite nano-bridge structure with a specific orientation on the surface of the coated graphite to obtain modified graphite.
[0035] Step S2 includes: S2.1. Evenly lay the coated graphite in a quartz boat, then place the quartz boat in a constant temperature zone of a tube furnace, evacuate the tube furnace, and introduce inert gas.
[0036] The coated graphite is evenly laid in the quartz boat to ensure uniform distribution of the sample; the tube furnace is evacuated and high-purity inert gas (such as nitrogen, argon or hydrogen) is introduced to effectively remove air and moisture, creating an oxygen-free, low-impurity reaction environment. The inert gas flow rate is controlled at 1~20L / min, which helps to maintain constant atmosphere pressure and temperature conditions, laying a stable foundation for subsequent chemical vapor deposition (CVD), thereby ensuring the uniformity and orientation of the deposited layer.
[0037] S2.2, raise the temperature to 500-1400°C at a heating rate of 0.5-5°C / min, maintain the temperature and continuously introduce carbon source gas for chemical vapor deposition, adjust the ambient pressure to 10-50Pa, control the deposition time to 30-120 minutes, and generate a graphite nano-bridge structure oriented in the same direction as the gas flow. The graphite nano-bridge structure can be 10-30nm.
[0038] The temperature is raised to 500~1400℃ at a heating rate of 0.5~5℃ / min. This slow and precise heating method allows the sample to fully adapt to temperature changes during the deposition process, which helps to form a good lattice arrangement. The carbon source gas (for example: ethylene and hydrogen are mixed in a ratio of 2:1, methane and hydrogen are mixed in a ratio of 4:1, or acetylene and hydrogen are mixed in a ratio of 1:1) is continuously introduced for deposition under a controlled low ambient pressure (10~50Pa), which causes the carbon source molecules to decompose and recombine in an orderly manner on the surface of the coated graphite, forming a graphite nano-bridge structure with a specific orientation. The deposition time is controlled at 30~120 minutes, which can accurately control the thickness and structural quality of the deposited layer, ensuring that the generated graphene layer has both good conductivity and mechanical support and interface buffering.
[0039] In one embodiment, step S2.2 further includes: Preheat the nitrogen-containing organic precursor to a temperature of 300-400°C to obtain a nitrogen-containing organic precursor gas, maintain the pressure of the tube furnace and adjust the temperature in the tube furnace to 500-800°C, maintain the temperature and continuously introduce the nitrogen-containing organic precursor gas for chemical vapor deposition for 1-2 hours, and generate a graphite phase carbon nitride film on the graphite nano-bridge structure. The graphite phase carbon nitride film can be 10-15nm. The nitrogen-containing organic precursor includes at least one of diurea diamine, urea, cyanamide, guanidine carbonate, and melamine.
[0040] By preheating the nitrogen-containing organic precursor to generate precursor gas, a uniform and dense graphite phase carbon nitride film can be formed on the surface of the graphite nano-bridge structure. This film not only improves the interface adhesion, but also effectively fills the micropores and improves the stability of the overall interface.
[0041] Combined with the oriented graphene bridging structure in step S2.2, it complements the graphene phase carbon nitride film. The graphene bridging structure provides a continuous high-conductivity channel, while the graphene phase carbon nitride film plays the role of interface protection, buffering and inhibiting side reactions, thereby improving the overall electronic and ion transport performance of the material during rapid charging and discharging. The graphite phase carbon nitride film has good chemical stability and adhesion. After covering the surface of the graphite nano-bridging structure, it can effectively isolate the direct contact between the electrolyte and the active material, reduce the occurrence of side reactions, and alleviate the stress concentration caused by the volume change of the graphene bridging structure. This double-layer structure significantly improves the stability and cycle life of the electrode material under high rate and long cycle conditions.
[0042] Both processes use chemical vapor deposition technology, which can achieve precise control of film thickness, crystallinity and orientation by finely regulating temperature, heating rate, reaction pressure, gas composition and deposition time. Whether it is graphene bridging structure or graphite phase carbon nitride film deposition, chemical vapor deposition technology can obtain uniform and dense films on a large area, ensuring that the final composite material has a continuous, efficient conductive network and a stable interface structure. Both processes are carried out under the protection of inert gas to avoid oxidation and contamination, while helping to enhance the adhesion between the deposited film and the substrate, and improve the overall mechanical stability and durability of the material. The chemical vapor deposition process has high repeatability and scalability potential. Both deposition processes are suitable for the uniform deposition of large-area films, providing reliable technical guarantees for industrial production.
[0043] In order to accurately control the thickness of the graphite nano-bridge structure and the graphite phase carbon nitride film, the control equation is as follows: The thickness control equation of the graphite nano-bridge structure is: in, is the thickness of the graphene nano-bridge structure (nm), is the reference thickness of the graphene nano-bridge structure (nm), indicating the critical temperature and critical pressure The deposition time is The thickness obtained when is the actual deposition temperature of the graphene nano-bridge structure (K), is the actual deposition pressure of the graphite nano-bridge structure (Pa), t is the deposition time of the graphite nano-bridge structure (minutes), is the empirical constant (dimensionless) of graphite nano-bridging structure, reflecting the effect of temperature and pressure deviation on deposition rate. It is 0.5~1.2.
[0044] By controlling the deposition temperature, pressure and deposition time, a graphite nano-bridge structure with good orientation and uniform distribution can be effectively formed; The value can adjust the density and arrangement of the bridging structure under different process conditions, thereby improving the conductivity and mechanical strength of the material; by optimizing the combination of T, P, and t, the thickness of the bridging structure can be controlled, thereby adjusting the specific surface area of the material and the internal ion diffusion path.
[0045] The thickness control equation of graphite phase carbon nitride film is: in, is the thickness of graphite carbon nitride film (nm), is the reference thickness of graphite carbon nitride film (nm), indicating the critical temperature and critical pressure The deposition time is The thickness obtained when is the actual deposition temperature of graphite phase carbon nitride film (K), is the actual deposition pressure of graphite phase carbon nitride film (Pa), t is the deposition time of graphite phase carbon nitride film (minutes), is the empirical constant (dimensionless) of graphite phase carbon nitride film, reflecting the effect of temperature and pressure deviation on deposition rate. It is 0.8~1.5.
[0046] By controlling the deposition temperature and pressure, a uniform and dense graphite phase carbon nitride film can be effectively formed; Adjust appropriately The value of can be used to optimize the density and thickness of the film under different process conditions, reduce pores and defects, and improve the chemical stability and conductivity of the material.
[0047] By setting the reference temperature and reference pressure, and using different and The deposition thickness of graphite bridge structure and carbon nitride film can be precisely controlled within the nanometer range. and By adjusting the deposition parameters, it is possible to adapt to different substrates and gas combinations, making it suitable for industrial-scale production.
[0048] S2.3. After the deposition is completed, stop introducing the carbon source gas and introduce only the inert gas. Keep the temperature for 1 to 20 hours, then slowly cool the temperature to 100 to 800°C at a cooling rate of 0.5 to 5°C / min, and then naturally cool the temperature to room temperature to obtain modified graphite.
[0049] After the deposition is completed, the carbon source gas is stopped and only inert gas is introduced, and the temperature is kept at high temperature for 1 to 20 hours. This process plays an annealing role, promotes the repair of graphene crystal defects, and enhances its crystallinity and conductivity. The temperature is slowly reduced to 100~800℃ at a cooling rate of 0.5~5℃ / min, and then naturally cooled to room temperature to ensure that thermal stress is slowly released and prevent structural stress concentration and crack formation caused by rapid cooling, thereby maintaining the integrity and stability of the modified graphite layer. The modified graphite obtained by the comprehensive annealing and slow cooling process has a highly ordered, uniform and highly crystalline graphite bridging structure. This structure significantly improves the overall conductivity, mechanical strength and cycle stability of the material, and has a direct positive impact on subsequent battery performance.
[0050] The inert gas includes at least one of nitrogen, argon, and hydrogen, the flow rate of the inert gas is 1~20L / min, and the carbon source gas includes at least one of ethylene and hydrogen in a volume ratio of 2:1, methane and hydrogen in a volume ratio of 4:1, and acetylene and hydrogen in a volume ratio of 1:1.
[0051] In step S2, by precisely controlling the conditions of vapor deposition, the carbon source molecules can be nucleated and orderly grown in a specific direction on the surface of the coated graphite, thereby forming a graphite nano-bridge structure with a specific orientation. The gas flow direction in the reaction chamber has a guiding effect on the transport of the carbon source molecules. The stable laminar flow state and uniform gas flow rate can make the carbon source molecules deposit uniformly along the direction of the gas flow, thereby forming an orderly oriented growth pattern on the substrate. After the coated graphite is pre-treated, its surface has a specific micro-roughness and energy distribution, which provides a selective deposition site for carbon atoms. Areas with lower surface energy are more likely to form initial nuclei, and these nuclei will expand along the lowest energy path and eventually present a specific orientation. The slow and uniform heating and low pressure environment in the temperature control system help control the dissociation and deposition rate of the carbon source molecules. The lower pressure and uniform temperature field reduce the probability of random deposition, so that the carbon atoms are arranged in an orderly manner along a favorable direction on the substrate.
[0052] The carbon source concentration in the carbon source gas (such as a mixture of ethylene, methane or acetylene and hydrogen) and the auxiliary effect of hydrogen are crucial to inhibiting the formation of amorphous carbon and promoting the growth of ordered graphene. Hydrogen helps to remove disordered carbon atoms adsorbed on the surface, thereby facilitating the formation of regular graphene layers. At the same time, the control of the gas flow rate ensures the continuous supply and uniform diffusion of the reactants.
[0053] S3, preparing a silicon-carbon substrate and mixing it with modified graphite to obtain a composite carbon layer-coated graphite-matched silicon-carbon material.
[0054] Step S3 includes: S3.1. Mix a porous carbon precursor with a silicon source material, raise the temperature to 400-700°C at a rate of 2-5°C / min under the protection of an inert gas, and keep the temperature for 2-4 hours to obtain a silicon-carbon substrate; the porous carbon precursor includes at least one of biomass carbon, asphalt carbon, and resin carbon, and the silicon source material includes at least one of sodium silicate, tetraethoxysilane, and nano-silicon powder. Calculated by mass ratio, the porous carbon precursor: silicon source = (2-5):1, and the silicon-carbon substrate includes internal pores and nano-silicon particles located in the internal pores, the size of the nano-silicon particles is 0.1-50nm, and the size of the internal pores is 0.1-100nm.
[0055] The porous carbon precursor and the silicon source material are mixed in a mass ratio and heated under the protection of an inert gas, so that the silicon source material can be evenly distributed in the pores of the carbon precursor and partially reduced to generate silicon nanoparticles. This not only ensures that the size of the nano-silicon particles is controlled within the range of 0.1~50nm, but also forms a rich porous structure, which is conducive to the rapid diffusion and storage of lithium ions. In this process, the high specific surface area of the porous carbon precursor provides sufficient dispersion space for the silicon source material, while helping to build an efficient conductive network, further improving the overall conductivity and cycle stability of the composite material. By slowly heating up and properly keeping warm, the chemical reaction can be carried out evenly, avoiding local overheating or agglomeration of the silicon source material, thereby ensuring the uniform structure of the silicon-carbon substrate and reducing the interfacial stress caused by structural unevenness in the subsequent mixing process.
[0056] S3.2. Mix the silicon-carbon substrate and the modified graphite in a VC mixer according to a specific mass ratio. Set the VC mixer revolution speed to 20-120 r / min and rotation speed to 40-180 r / min. Mix for 0.5-~4 hours to obtain a composite carbon layer-coated graphite matching silicon-carbon material.
[0057] The prepared silicon-carbon substrate and modified graphite are mixed in a VC mixer. By setting reasonable revolution (20120r / min) and rotation speed (40180r / min) and mixing time (0.5~4 hours), the two materials can be fully and evenly dispersed at the macro and micro levels to form a compact composite structure. During the mixing process, mechanical shearing can effectively break the agglomeration phenomenon that may exist on the surface of the material, enhance the interface bonding between silicon-carbon and modified graphite, thereby improving the conductivity and mechanical strength of the overall composite material and optimizing the interface stability of the battery during charging and discharging. Uniform mixing ensures that the silicon-carbon substrate can be evenly dispersed in the graphite matrix, thereby forming a continuous and efficient lithium ion transmission channel when the battery is working, while alleviating the volume expansion problem of silicon during charging and discharging, and ultimately achieving high rate and long cycle life.
[0058] The present invention provides a composite carbon layer-coated graphite-matched silicon-carbon material, which is prepared by a preparation method of a composite carbon layer-coated graphite-matched silicon-carbon material. The composite carbon layer-coated graphite-matched silicon-carbon material comprises asphalt, a graphite substrate, a graphite nano-bridge structure, and a silicon-carbon substrate; wherein: The pitch is used to form a coated carbon layer and optimize the interface bonding between the coated carbon layer and the graphite substrate; The graphite substrate is used to provide a stable conductive skeleton and structural support; The graphite nano-bridge structure is used to strengthen the conductive network, enhance the overall structural stability and conductivity of the material, and effectively buffer the stress of lithium ions during the charging and discharging process; The silicon-carbon substrate is used to increase the overall theoretical specific capacity of the material while buffering the volume expansion of silicon during the charging and discharging process.
[0059] The following are various embodiments and comparative examples of the present invention.
[0060] Embodiment 1: Weigh 0.4g of asphalt with a β resin content of 40wt.% and place it in 300mL of anhydrous ethanol for ultrasonic dispersion for 30min. Transfer the solution to a water bath, heat it to 90°C, add 20g of graphite (the raw materials are needle coke and secondary particles) to the above solution and stir, and keep 90°C until the anhydrous ethanol is completely volatilized. Transfer the evaporated material to a vacuum oven for drying. After coating, add the sample to a tube furnace, pass nitrogen at a flow rate of 0.2L / min, pass the carbon source gas to heat up to 1250° at 2°C / min and keep it warm for 4h, then pass the nitrogen-containing organic precursor gas to 800°C, and then cool it naturally. After carbonization, place the sample in a VC mixer, add 3g of silicon-carbon substrate, and the mixing parameters are as follows: revolution speed 60r / min, rotation speed 120r / min, and mix for 2h. Obtain a composite carbon layer coated with graphite matching silicon-carbon material.
[0061] Embodiment 2: Weigh 1.2g of asphalt with a β resin content of 50wt.% and place it in 300mL of anhydrous ethanol for ultrasonic dispersion for 30min. Transfer the solution to a water bath, heat it to 90°C, add 20g of graphite (raw materials are petroleum coke and secondary particles) to the above solution and stir, and keep 90°C until the anhydrous ethanol is completely volatilized. Transfer the evaporated material to a vacuum oven for drying. After coating, add the sample to a tube furnace, pass nitrogen at a flow rate of 0.2L / min, pass the carbon source gas to heat up to 1200° at 2°C / min and keep warm for 4h, then pass the nitrogen-containing organic precursor gas to 800°C, and then cool naturally. After carbonization, place the sample in a VC mixer, add 3g of silicon-carbon substrate, and the mixing parameters are as follows: revolution speed 60r / min, rotation speed 120r / min, and mix for 2h. Obtain a composite carbon layer coated with graphite matching silicon-carbon material.
[0062] Embodiment 3: Weigh 10g of asphalt with a β resin content of 40wt.% and place it in 3L of anhydrous ethanol for ultrasonic dispersion for 30min. Transfer the solution to a water bath, heat it to 90°C, add 500g of graphite (the raw materials are needle coke and secondary particles) to the above solution and stir, and keep 90°C until the anhydrous ethanol is completely volatilized. Transfer the evaporated material to a vacuum oven for drying. After coating, add the sample to a tubular furnace, pass nitrogen at a flow rate of 0.2L / min, pass the carbon source gas to heat it to 1250° at 2°C / min and keep it for 4h, then drop it to 800°C, and then cool it naturally. After carbonization, place the sample in a VC mixer, add 50g of silicon-carbon substrate, and the mixing parameters are as follows: revolution speed 60r / min, rotation speed 120r / min, and mix for 2h. Obtain a composite carbon layer coated with graphite matching silicon-carbon material.
[0063] Embodiment 4: Weigh 20g of asphalt with a 40wt.% beta resin content and place it in 3L of anhydrous ethanol for ultrasonic dispersion for 30min. Transfer the solution to a water bath, heat it to 90°C, add 500g of graphite (raw materials are petroleum coke and primary particles) to the above solution and stir, and keep 90°C until the anhydrous ethanol is completely volatilized. Transfer the evaporated material to a vacuum oven for drying. After coating, add the sample to a tubular furnace, pass nitrogen at a flow rate of 0.2L / min, pass the carbon source gas at 2°C / min to 1250° for 4h, then drop to 800°C, and then cool naturally. After carbonization, place the sample in a VC mixer, add 100g of silicon-carbon substrate, and the mixing parameters are as follows: revolution speed 60r / min, rotation speed 120r / min, and mix for 4h. Obtain a composite carbon layer coated with graphite matching silicon-carbon material.
[0064] Embodiment 5: Weigh 150g of asphalt with a 45wt.% beta resin content and 5000g of graphite (raw materials are petroleum coke and primary particles) and place them in a VC mixer. Set the revolution speed of the VC mixer to 50r / min, the rotation speed to 100r / min, and the mixing time to 5h to fully mix the asphalt and graphite. After coating, add the sample to a tubular furnace, pass nitrogen at a flow rate of 0.2L / min, pass the carbon source gas to heat up to 1250° at 2°C / min and keep warm for 4h, then drop to 800°C, and then cool naturally. After carbonization, place the sample in a VC mixer, add 500g of silicon-carbon substrate, and the mixing parameters are as follows: revolution speed 60r / min, rotation speed 120r / min, and mix for 4h. Obtain a composite carbon layer coated with graphite matching silicon-carbon material.
[0065] Comparative Example 1: Weigh 20g of graphite (the raw materials are needle coke and secondary particles) and place it in a VC mixer, add 3g of silicon-carbon substrate, and the mixing parameters are as follows: revolution speed 60r / min, rotation speed 120r / min, and mix for 2h. Uncoated graphite matching silicon-carbon material is obtained.
[0066] Electrochemical performance test: Electrode preparation: weigh the above composite material, conductive carbon black, and binder CMC in proportion, add deionized water to prepare a uniform slurry, wherein the solid content ratio of composite material: conductive carbon black: binder CMC is 95:1.5:3.5, and use a homogenizer to make the sample at a speed of 2000 rpm for 20 min.
[0067] The slurry was sieved and evenly coated on the copper foil, and placed in a 90°C vacuum drying oven for drying. The dried electrode was rolled and cut into circular electrodes of a certain size, and the electrode mass was recorded.
[0068] Button battery assembly: In an argon atmosphere glove box, a metal lithium sheet is used as a counter electrode and assembled into a button battery with the above-obtained electrode, diaphragm, gasket, etc., and a silicon-carbon special electrolyte is used as the electrolyte.
[0069] The data results are summarized in Table 1. It can be seen that the graphite-matched silicon-carbon material coated with the composite carbon layer provided in Example 2 has a first-cycle reversible capacity of 533.6 mAh / g and a first coulombic efficiency of 93.03%. After 100 cycles, the reversible capacity is 489.4 mAh / g and the capacity retention rate is 91.72%, which has excellent cycle performance and first-cycle coulombic efficiency.
[0070] Table 1: Performance test results of embodiments and comparative examples Figure 1 The TEM image of the composite carbon layer coated with graphite matching silicon-carbon material. The clarity of the interlayer distance and stacking structure reflects the crystallinity and orientation of the material.
[0071] Figure 2 It is the X-ray diffraction (XRD) pattern of the material under different experimental conditions. There are multiple characteristic diffraction peaks in the XRD spectrum, indicating that the material has a highly ordered crystal structure. The position of the diffraction peak can determine the lattice constant, crystallinity and orientation of the material. The XRD peak displacement or peak intensity change of different samples illustrates the regulatory effect of different deposition conditions on the material structure. The diffraction peaks of Examples 1-5 are sharp, indicating that the material has a higher degree of crystallinity. The peak position is stable and the diffraction peaks are evenly spaced, indicating that the material structure is complete. The higher the diffraction peak intensity, the higher the orientation and the better the interlayer stacking of the material. The diffraction peak intensity of Comparative Example 1 is lower, indicating that there are more disorder or defects inside the material.
[0072] Figure 3 The Raman spectra of the materials obtained under different experimental conditions are shown. The Raman spectra contain D peak (located at about 1350cm⁻¹) and G peak (located at about 1580cm⁻¹). and The ratio represents the degree of graphitization and defect of the material. Too low indicates that the overall graphitization degree of the material is poor and the D peak is weak. Too low, the right amount of defects in graphene or graphite materials can introduce more electron migration paths in the material structure and provide active sites for the diffusion of lithium ions. If the ratio is too low, although the material has higher structural integrity and mechanical strength, the electron / ion migration rate may be limited. By comparing the ratios between different samples, the effect of the preparation conditions on the structural integrity and the number of defects of the material can be judged. Examples 1-5 all show obvious G peaks and D peaks, indicating that the material has a graphite or graphene structure. The D peak and G peak signals of the comparative example are very weak, indicating that the material has serious structural defects, a large amount of disordered stacking, and a poor degree of graphitization.
[0073] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material, characterized in that the steps include: S1, coating asphalt on a graphite substrate to obtain coated graphite; S2, introducing a carbon source gas to perform chemical vapor deposition on the coated graphite, generating a graphite nano-bridge structure with a specific orientation on the surface of the coated graphite, and obtaining modified graphite; S3, preparing a silicon-carbon substrate and mixing it with the modified graphite to obtain a composite carbon layer-coated graphite-matched silicon-carbon material.
2. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 1, characterized in that: In step S1, the graphite substrate includes at least one of natural graphite, primary graphite particles, secondary graphite particles, needle coke graphite, petroleum coke graphite, raw coke graphite, and cooked coke graphite, and the asphalt includes β resin, and the content of the β resin in the asphalt is 10-80%.
3. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 1, characterized in that: Step S1 includes: S1.
1. Ultrasonic dispersion of asphalt in anhydrous ethanol for 15 to 60 minutes to form an asphalt emulsion; S1.2, transfer the asphalt emulsion to a constant temperature water bath, add the graphite substrate to the asphalt emulsion under the condition of controlling the temperature at 40-90°C, control the stirring speed at 300-500 rpm, and continue stirring for 1-3 hours until the anhydrous ethanol is completely evaporated; S1.
3. After stirring, transfer to a vacuum oven and continue vacuum drying at 60-80°C for 12-24 hours to obtain coated graphite.
4. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 1, characterized in that: Step S1 includes: S1.1, preheating the asphalt to 80-120°C and stirring for 30-90 minutes, while adding graphene or carbon nanotubes to obtain rheological asphalt; S1.
2. The rheological asphalt and the graphite substrate are mixed in the solid phase in a VC mixer. The revolution speed of the VC mixer is set to 30-150 r / min, the rotation speed is set to 50-200 r / min, and the mixing time is set to 0.5-5 hours. During the mixing process, ultrasonic assisted dispersion with a frequency of 20-40 kHz is intermittently used. The ultrasonic treatment time for each time is 10-20 minutes. After the mixing is completed, the coated graphite is obtained.
5. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 3 or 4, characterized in that: Calculated by weight percentage, in the coated graphite, the asphalt accounts for 10-40wt%, and the graphite substrate accounts for 60-90%.
6. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 1, characterized in that: Step S2 includes: S2.1, the coated graphite is evenly laid in a quartz boat, and then the quartz boat is placed in a constant temperature zone of a tube furnace, the tube furnace is evacuated, and an inert gas is introduced; S2.2, raising the temperature to 500-1400°C at a heating rate of 0.5-5°C / min, maintaining the temperature and continuously introducing carbon source gas for chemical vapor deposition, adjusting the ambient pressure to 10-50 Pa, and controlling the deposition time to 30-120 minutes, to generate a graphite nano-bridge structure oriented in the same direction as the gas flow; S2.
3. After the deposition is completed, stop introducing the carbon source gas and introduce only the inert gas. Keep the temperature for 1 to 20 hours, then slowly cool the temperature to 100 to 800°C at a cooling rate of 0.5 to 5°C / min, and then naturally cool the temperature to room temperature to obtain modified graphite.
7. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 6, characterized in that: In step S2, the inert gas includes at least one of nitrogen, argon, and hydrogen, the flow rate of the inert gas is 1~20L / min, and the carbon source gas includes at least one of ethylene and hydrogen in a volume ratio of 2:1, methane and hydrogen in a volume ratio of 4:1, and acetylene and hydrogen in a volume ratio of 1:
1.
8. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 1, characterized in that: Step S3 includes: S3.1, mixing the porous carbon precursor with the silicon source material, raising the temperature to 400-700°C at 2-5°C / min under the protection of an inert gas, and keeping the temperature for 2-4 hours to obtain a silicon-carbon substrate; S3.
2. Mix the silicon-carbon substrate and the modified graphite in a VC mixer at a specific mass ratio, set the VC mixer revolution speed to 20-120 r / min, rotation speed to 40-180 r / min, mix for 0.5-~4 hours, and obtain a composite carbon layer-coated graphite matching silicon-carbon material.
9. The method for preparing a composite carbon layer-coated graphite-matched silicon-carbon material according to claim 8, characterized in that: In step S3, the porous carbon precursor includes at least one of biomass carbon, asphalt carbon, and resin carbon, and the silicon source material includes at least one of sodium silicate, tetraethoxysilane, and nano-silicon powder. Calculated by mass ratio, the porous carbon precursor: the silicon source = (2~5): 1, and the silicon-carbon substrate includes internal pores and nano-silicon particles located in the internal pores. The size of the nano-silicon particles is 0.1~50nm, and the size of the internal pores is 0.1~100nm.
10. A composite carbon layer coated graphite matching silicon-carbon material, characterized in that: It is made by the preparation method of the composite carbon layer coated graphite matching silicon-carbon material according to any one of claims 1 to 9, wherein the composite carbon layer coated graphite matching silicon-carbon material comprises asphalt, a graphite substrate, a graphite nano-bridge structure, and a silicon-carbon substrate; wherein, The pitch is used to form a coated carbon layer and optimize the interface bonding between the coated carbon layer and the graphite substrate; The graphite substrate is used to provide a stable conductive skeleton and structural support; The graphite nano-bridge structure is used to strengthen the conductive network, enhance the overall structural stability and conductive properties of the material, and effectively buffer the stress of lithium ions during the charging and discharging process; The silicon-carbon substrate is used to increase the theoretical specific capacity of the entire material and buffer the volume expansion of silicon during the charge and discharge process.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode material of lithium ion battery
CN109713268A
Silicon-graphite composite electrode active material for lithium secondary battery, electrode and lithium secondary battery comprising same, and method for producing said silicon-graphite composite electrode active material
CN111418096A
Cited By
Carbon material and preparation method and application thereof
CN122301208A